Evidence for intergranular tunnelling in polyaniline passivated alpha-Fe nanoparticles - Sunny, Vijutha; Narayanan, T. N.; Sajeev, U. S.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Nanoparticles are of immense importance both from the fundamental and application points of view. They exhibit quantum size effects which are manifested in their improved magnetic and electric properties. Mechanical attrition by high energy ball milling (HEBM) is a top down process for producing fine particles. However, fineness is associated with high surface area and hence is prone to oxidation which has a detrimental effect on the useful properties of these materials. Passivation of nanoparticles is known to inhibit surface oxidation. At the same time, coating polymer film on inorganic materials modifies the surface properties drastically. In this work a modified set-up consisting of an RF plasma polymerization technique is employed to coat a thin layer of a polymer film on Fe nanoparticles produced by HEBM. Ball-milled particles having different particle size ranges are coated with polyaniline. Their electrical properties are investigated by measuring the dc conductivity in the temperature range 10-300 K. The low temperature dc conductivity (I-V) exhibited nonlinearity. This nonlinearity observed is explained on the basis of the critical path model. There is clear-cut evidence for the occurrence of intergranular tunnelling. The results are presented here in this paper.